2005
DOI: 10.1152/ajpheart.00525.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite is an alternative source of NO in vivo

Abstract: In this study, we investigated whether orally administered nitrite is changed to NO and whether nitrite attenuates hypertension in a dose-dependent manner. We utilized a stable isotope of [15N]nitrite (15NO2-) as a source of nitrite to distinguish between endogenous nitrite and that exogenously administered and measured hemoglobin (Hb)-NO as an index of circulating NO in whole blood using electron paramagnetic resonance (EPR) spectroscopy. When 1 mg/kg Na15NO2 was orally administered to rats, an apparent EPR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 91 publications
(93 reference statements)
2
106
1
11
Order By: Relevance
“…Mechanisms of tissue uptake and distribution of nitrite remain poorly understood (32). However, we found distinct differences in blood and tissue nitrite levels in response to sodium nitrite therapy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Mechanisms of tissue uptake and distribution of nitrite remain poorly understood (32). However, we found distinct differences in blood and tissue nitrite levels in response to sodium nitrite therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Recent reports demonstrate that administration of nitrite results in rapid accumulation of this anion in plasma and blood (32,33). Fig.…”
Section: Chronic Sodium Nitrite Therapy Increases Ischemic Endotheliamentioning
confidence: 95%
“…Nitrite is a major storage form of nitric oxide (NO) in blood and tissues (14). Oral nitrite reverses N G -nitro-L-arginine methyl ester-induced hypertension and serves as an alternate source of NO in vivo (91). Further, plasma nitrite levels progressively decrease with increasing cardiovascular risk (52).…”
Section: Nitric Oxidementioning
confidence: 99%
“…In bacteria intracellular nitrate concentration is regulated by active membrane transport and dentification cascades [84]. However, in hypoxic condition of upper alimentary canal bacterial conversion of dietary nitrate to nitrite may be a prevalent source of nitrite and consequently of NO for proximal tissues and entire organisms [85,86]. For example, eNOS itself may effectively reduce nitrite to NO under anoxic conditions [27], and similar biases are quite possible in other tissues.…”
Section: Enzymatic Reduction Of Nitrogen Oxides-mentioning
confidence: 99%
“…Homologous components for nitrate/nitrite transport are largely unknown in organisms, but there is some evidence of nitrite transport via a Cl − / HCO 3 − exchanger [119] which is member of the bicarbonate transporter family (SLC4). Nevertheless, it has been shown that dietary nitrate [86,120,121] as well as symbiotic and/or pathogenic bacteria immobilized nitrate [88,[122][123][124] may play an important role in the formation of nitrite at pathogenic and normal levels and consequently in regulating NO pools in higher organisms.…”
Section: No Oxidation Product and Nitrite Reductase Substrate Nitritmentioning
confidence: 99%